Implantable cardioverter-defibrillator therapy among patients with non-ischaemic vs. ischaemic cardiomyopathy for primary prevention of sudden cardiac death. Issue 1 (11th January 2017) - Amara, Nelly; Boveda, Serge; Defaye, Pascal; Klug, Didier; Treguer, Fréderic; Amet, Denis; Perier, Marie-Cécile; Gras, Daniel; Algalarrondo, Vincent; Bouzeman, Abdeslam; Piot, Olivier; Deharo, Jean-Claude; et al.
Abstract: Aim: The magnitude of benefit related to implantable cardioverter defibrillator (ICD) therapy for primary prevention of sudden cardiac death (SCD) in non-ischaemic cardiomyopathy (NICM) and ischaemic cardiomyopathy (ICM) has not been evaluated extensively in clinical practice. Methods and results: Of the 5539 consecutive patients enrolled in the multicentre Défibrillateur Automatique Implantable–Prévention Primaire (DAI-PP) study (2002–12), 5485 patients (with information on underlying heart disease) were included in the present analysis: 2181 (39.8%) had NICM and 3304 (60.2%) had ICM. ICM patients were older (63.7 ±10.3 vs. 60.6 ± 12.2 years, P < 0.0001), with a higher ejection fraction [27% (25–30) vs. 25% (20–30), P < 0.0001], narrower QRS (37.3% vs. 21.4% with QRS <120, P < 0.0001), and higher prevalence of sinus rhythm (77.3% vs. 74.0%, P = 0.009). During a mean follow-up of 3.1 ± 2.2 years, 814 patients died, giving a mortality incidence of 48.6 per 1000 person-years [95% confidence interval (CI) 45.2–51.9], higher among ICM patients (52.3, 95% CI 47.8–56.7) than in NICM patients (42.4, 95% CI 37.3–47.6; P = 0.008) (adjusted hazard ratio 1.31, 95% CI 1.06–1.61, P = 0.01). The increase in mortality among ICM patients was mainly due to non-cardiovascular mortality ( P = 0.0002), whereas incidences of cardiovascular mortality (including ICD-unresponsive SCD) were similar in the two groups. Incidences of appropriate ICD interventions (anti-tachycardia pacing, shocks) were similar, but inappropriate therapies were more frequent in NICM (7.94 vs. 5.96%; P = 0.005). Conclusion: NICM and ICM patients had a same rate of ICD therapy for primary prevention of SCD in everyday practice. But, ICM patients more often died of a non- cardiovascular cause of death. Clinical Trial Registration: NCT 01992458.